Regional inequalities in African political economy: Theory, conceptualization and measurement, and political effects - Catherine Boone; Rebecca Simson (London School of Economics and Political Science (LSE), Department of International Development, 2019)
There is growing recognition in the economics literature that African countries are characterized by very large economic disparities across subnational regions. Yet the lack of systematic and reliable empirical data at subnational levels of aggregation has made it difficult to explore possible links between these spatial inequalities and political dynamics. This paper reviews some of the empirical literature that attempts to measure and compare spatial inequality within and acorss African countries, and asks whether and how it might be used to bring studies of Africa into dialogue with comparative political economy work on regional inequality in other parts of the world.
Keywords: 330; Africa; Inequality; Regionalism; Political geography; Urban-rural; Political economy